Pengaruh Bermain Game Online Terhadap Perilaku Komunikasi Siswa Kelas XII Jurursan Mipa SMA Negeri 1 Andong - Fina Izdni Rahmawati; Harjanti Jabal; Rizki Pratama (Publikasi Indonesia, 2022)
This study aims to determine and analyze the Effect of Online Game on Communication Behavior of Students SMA Negeri 1 Andong. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. Data were analyzed using simple regression analysis. The population of this research is the XII grade field of mathematics and natural sciences students of SMA Negeri 1 Andong with a total of 300 students in which only 26% or 78 students were sampled for this study. The results of this study indicate that the online game have no effect on communication behavior.